Metal-catalyzed hydrolysis of ammonia borane: Mechanism, catalysts, and challenges. (6th November 2020) - Wu, Han; Cheng, Yaojia; Fan, Yanping; Lu, Xingmei; Li, Lixin; Liu, Baozhong; Li, Baojun; Lu, Siyu
Abstract: Ammonia borane is a promising material for hydrogen storage. In particular, its metal-catalyzed hydrolysis, which can occur under mild conditions and release a high amount (7%–8%) of hydrogen, has attracted considerable recent attention. Most previous studies have sought to improve the hydrolysis rate, leading to a relatively asymmetric research trend, where some potential problems must be overcome before its industrialization. A comprehensive analysis and systematic overview of current research would therefore be helpful to future works. This review first discusses the hydrolysis of ammonia borane in detail. It then summarizes and analyzes recent development of metal catalysts. Some challenges related to the hydrolysis system are also discussed, and finally, some perspectives on emerging issues regarding the future development of this system are provided. Graphical abstract: The hydrolysis of ammonia borane is a potentially efficient method of hydrogen production due to its mild conditions and high hydrogen emission. The recent development of many metal catalysts has enlivened this research area. However, increasing the hydrolytic kinetics of ammonia borane has revealed some potential problems, which must be overcome before ammonia borane can be widely used. Therefore, this review considers ammonia borane as a hydrogen storage material, examining its physicochemical properties and hydrolysis mechanism. Recent developments of metal catalysts are discussed, as well as the challenges facing the application of ammonia borane hydrolysis systems. Finally, some perspectives regarding emerging issues for future research are provided. Image 1 Highlights: The properties and hydrolysis mechanism of ammonia borane are discussed here. The popular metal catalysts developed in recent years were classified and analyzed. Some challenges and exploratory work related to the hydrolysis system are introduced. Some perspectives regarding the future development of this system are provided.